The person and the teacher: A case study into language teacher identity formation - Tran, Ba-Linh; Sánchez, Hugo Santiago (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Research in mainstream and language teacher education has underlined the importance of understanding teacher identity. As part of a larger investigation, this study examined the identity formation of two Vietnamese English teachers via a case study design using background and auto-biographical semi-structured interviews. The findings reinforce the conclusions drawn in some previous studies about teacher identity formation being a complex process involving professional and personal factors. Additionally, however, the results shed light on the role of formal and informal pre-training learning experiences both inside and outside the classroom, in the formation of language teacher identity. The study thus expands our understanding of teacher identity and calls for a more holistic perspective that acknowledges this multiplicity of prior learning experiences as well as the professional and personal dimensions of this construct.